Chronic restraint stress during withdrawal increases vulnerability to drug priming-induced cocaine seeking via a dopamine D1-like receptor-mediated mechanism. (1st June 2018) - Ball, Kevin T.; Stone, Eric; Best, Olivia; Collins, Tyler; Edson, Hunter; Hagan, Erin; Nardini, Salvatore; Neuciler, Phelan; Smolinsky, Michael; Tosh, Lindsay; Woodlen, Kristin
Highlights: The effect of chronic restraint stress on subsequent cocaine seeking was tested. Both extinction- and abstinence-based animal relapse models were used. Chronic restraint stress caused increase in cocaine priming-induced reinstatement. A dopamine D1 -like receptor antagonist, combined with stress, attenuated this effect. Prior antagonist treatment resulted in increased cue-induced reinstatement. Abstract: Background: A major obstacle in the treatment of individuals with cocaine addiction is their high propensity for relapse. Although the clinical scenario of acute stress-induced relapse has been well studied in animal models, few pre-clinical studies have investigated the role of chronic stress in relapse or the interaction between chronic stress and other relapse triggers. Methods: We tested the effect of chronic restraint stress on cocaine seeking in rats using both extinction- and abstinence-based animal relapse models. Rats were trained to press a lever for I.V. cocaine infusions (0.50 mg/kg/infusion) paired with a discrete tone + light cue in daily 3-h sessions. Following self-administration, rats were exposed to a chronic restraint stress procedure (3 h/day) or control procedure (unstressed) during the first seven days of a 13-day extinction period during which lever presses had no programmed consequences. This was followed by cue- and cocaine priming-induced drug seeking tests. In a separate group of rats, cocaine seeking was assessed during forced abstinence both before and after the same chronic stress procedure. Results: A history of chronic restraint stress was associated with increased cocaine priming-induced drug seeking, an effect attenuated by co-administration of SCH-23390 (10.0 μg/kg; i.p.), a dopamine D1 -like receptor antagonist, with daily restraint. Repeated SCH-23390 administration but not stress during extinction increased cue-induced reinstatement. Conclusions: Exposure to chronic stress during early withdrawal may confer lasting vulnerability to some types of relapse, and dopamine D1 -like receptors appear to mediate both chronic stress effects on cocaine seeking and extinction of cocaine seeking.